City and Territory in code of Contemporary Urban Scenery in Spain and Mexico - Cabrerizo Sanz, Casilda (Editorial Pontificia Universidad Javeriana, 2013)
This article considers the daily scenery of the contemporary city that explicitly shows the dislocation of the natural and social systems which creates barriers that fragment the territory. This hypothesis is stated after checking the territorial occupation patterns and the scenery created by the research experience on Mexican and Spanish cities. Their daily urban scenery is a sample of the (expansionist and consumer) predominant occupation pattern that has imposed an order to the territory and that makes tabula rasa of the historical and cultural past. A look between the research and the action, a dialogue between the user and the specialist dissection are proposed in order to identify and characterize the scenery, letting differentiate and individualize units. This is a diagnose of the highly deficient way the territory is managed and a proposal of a method that speeds up the use as a operative instrument for planning.